Contribution of Rural Sufism for Strengthening Pancasila Values; Case Study of the Qadiriyah-Naqsabandiyah Congregation in Lamongan - Sulhatul Habibah (Tribakti: Jurnal Pemikiran Keislaman, 2022)
The existence of rural Sufism strengthens the dimensions of spirituality and the values ​​of Pancasila. This paper analyzes the contribution of the Qadiriyah-Naqsabandiyah congregation in Kebonagung Village, Babat, Lamongan, for strengthening Pancasila values. From field observations, interviews, and activity analysis, this research found that the strengthening of Pancasila values ​​in Kebonagung village resulted from the moral awareness of the Qadiriyah-Naqsabandiyah congregation. The values of Pancasila are the value of divinity with the spirit of religiosity in worship and religious activities, human values ​​by maintaining Islamic brotherhood, the value of unity by creating strong social cohesion in society, populist values ​​with deliberation in solving problems, the value of justice with the spirit of sharing with others or alms. Strengthening the values ​​of Pancasila makes rural Sufism fulfill the requirements of being a good citizen. This study suggests that the rural Sufism movement is an essential part of supporting the existence of Pancasila from below.